The Gothenburg SOM Survey 2019 - SOM Institute, University of Gothenburg (University of Gothenburg, 2021)
In the autumn of 2019, the fourth edition of the Gothenburg SOM survey was conducted. A total of 5000 randomly selected citizens of Gothenburg answered questions about attitudes and habits in relation to society, opinion and media. Many of the questions in the Gothenburg survey are of a regional nature, and concern local politicians and infrastructure initiatives.

Hösten 2019 genomfördes för fjärde gången en SOM-undersökning i Göteborgs stad, där totalt 5000 slumpmässigt utvalda göteborgare fick svara på frågor om attityder och vanor i relation till samhälle, opinion och medier. Många av frågorna i Göteborgsundersökningen är av regional karaktär och rör lokala politiker, infrastruktursatsningar, och bilden av Göteborg som stad.
SOM-undersökningen i Göteborg 2019
Gbg-SOM 2019
Keywords: housing; boende; occupations; yrken; public sector; offentlig sektor; environment; miljö; consumption; konsumtion; public opinion; allmän opinion; environmental degradation; miljöförstörelse; trust; förtroende; european union; europeiska unionen; political interest; politiskt intresse; local government services; kommunal service; public transport; kollektivtrafik; medical care; sjukvård; public services; offentlig service; news; nyheter; privatization; privatisering; income; inkomst; political participation; politiskt deltagande; sick leave; sjukfrånvaro; religious practice; religionsutövning; democracy; demokrati; internal politics; inrikespolitik; political parties; politiska partier; Dental Care; Tandvård; internet use; internetanvändning; politicians; politiker; local government organizations; kommunala organisationer; social participation; socialt deltagande; working conditions; arbetsförhållanden; households; hushåll; local community facilities; lokala serviceinrättningar; clubs; föreningar; cultural activities; kulturaktiviteter; leisure time activities; fritidsaktiviteter; educational levels; utbildningsnivå; traffic; trafik; political attitudes; politiska åsikter; state health services; statlig hälso- och sjukvård; social networks; socialt nätverk; CORS; CORS; POLITICS; POLITIK; SOCIETY AND CULTURE; SAMHÄLLE OCH KULTUR; Elections; Val; Political behaviour and attitudes; Politiska beteenden och attityder; Political ideology; Politisk ideologi; Cultural activities and participation; Kulturaktiviteter och deltagande; Media; Media; MEDIA, COMMUNICATION AND LANGUAGE; MEDIA, KOMMUNIKATION OCH SPRÅK; LABOUR AND EMPLOYMENT; ARBETE OCH SYSSELSÄTTNING; Leisure, tourism and sport; Fritid, turism och sport